The effects of intensive speech treatment on intelligibility in Parkinson's disease: A randomised controlled trial. (July 2020) - Levy, Erika S.; Moya-Galé, Gemma; Chang, Young Hwa M.; Freeman, Katherine; Forrest, Karen; Brin, Mitchell F.; Ramig, Lorraine A.
Abstract: Background: More than 6, 000, 000 individuals worldwide are diagnosed with Parkinson's disease (PD). Nearly 90% develop speech signs that may substantially impair their speech intelligibility, resulting in losses in their communication and quality of life. Benefits of intensive speech treatment have been documented for a range of speech signs. However, the critical question of whether speech is more intelligible after treatment has not been investigated in a randomised controlled trial (RCT). We hypothesised that intensive speech treatment would improve speech intelligibility in PD. Method: Sixty-four patients with hypokinetic dysarthria secondary to PD participated in this single-centre, parallel arm, statistically-powered RCT. Reporting follows CONSORT guidelines for non-pharmacological treatment. Patients were recruited from US clinics and randomised using a statistician-derived minimisation algorithm, to intensive speech treatment (16 1-hour sessions/1 month) targeting voice (voice group) or targeting articulation (articulation group) or to an untreated group (no treatment group). Speech treatments were delivered by speech clinicians who specialised in treating patients with PD. Trial design minimised bias and supported equipoise. For intelligibility assessment, blinded listeners ( n = 117) orthographically transcribed 57 patients' recorded, self-generated narrative speech samples, randomly presented in multi-talker babble noise. Listeners were American-English speakers, ages 18–35 years, with normal hearing. The primary outcome was baseline (pre-treatment) to post-treatment change in transcription accuracy (TA), recognised as the most objective measure of intelligibility. TA was defined as the percentage of words transcribed correctly. Listeners, data collectors, and data managers were blinded to treatment conditions and groups. Reliability was evaluated using intraclass correlation coefficients and differences amongst groups were evaluated by mixed-effects models, in accordance with the intention-to-treat approach. This trial was registered with ClinicalTrials.gov Identifier: NCT00123084. Findings: Between June 23, 2016 and August 14, 2017, blinded listeners transcribed baseline and post-treatment speech samples for intelligibility assessment of 57 patients in the voice ( n = 19), articulation ( n = 19) and no treatment ( n = 19) groups. Between-group differences (d) in changes from baseline to post-treatment in TA indicated significantly greater increases following treatment targeting voice than treatment targeting articulation ( d = 26·2%, 95% CI 1·5 − 51·0; p = 0·04; ES=1·0). Differences between TA changes in the treatment targeting voice and in the no treatment group were significant ( d = 42·8%, 95% CI 22·4 − 63·2; p = 0·0002; ES=1·8). Differences between TA changes in the treatment targeting articulation and in the no treatment group were not significant ( d = 16·5%, 95% CI -6·1 − 39·2; p = 0·147; ES=0·9). Interpretation: These findings provide the first RCT evidence that intensive speech treatment targeting voice improves speech intelligibility in PD. Thus, this evidence-based treatment may positively impact health-related quality of life for patients with PD globally when it is included in patient management. Funding: NIH NIDCD R01 DC01150 and LSVT Global, Inc.